First report of long term measurements of the MGGL laboratory in the Mátra mountain range. (28th April 2017) - Barnaföldi, G G; Bulik, T; Cieslar, M; Dávid, E; Dobróka, M; Fenyvesi, E; Gondek-Rosinska, D; Gráczer, Z; Hamar, G; Huba, G; Kis, Á; Kovács, R; et al.
Abstract: Matra Gravitational and Geophysical Laboratory (MGGL) was established near Gyöngyösoroszi, Hungary in 2015, in the cavern system of an unused ore mine. The laboratory is located 88 m below the surface, with the aim of measuring and analysing the advantages of the underground installation's third generation gravitational wave detectors. Specialized instruments have been installed to measure seismic, infrasound and electromagnetic noise, and the variation of the cosmic muon flux. In the preliminary (RUN-0) test period, March–August 2016, data collection was accomplished. In this paper we describe the research potential of the MGGL, list the installed equipment and summarize the experimental results of RUN-0. Here we report on the RUN-0 data, that prepares the systematic and synchronized data collection of the next run period.